Implementasi Internet of Things Untuk Pembuatan Keyless Smart Door Dengan NFC Tag Dan QR Code - Jason Evander; Resmana Lim; Justinus Andjarwirawan (Universitas Kristen Petra, 2022)
Along with the current pandemic that’s been going on, most people will spend their time at home, and wants to feel comfortable and safe because they spend most of the time inside their house. Many burglary door cases happen because the lack of security at their homes.In this research, a trial will be conducted to help resolve the problem by implementing Internet of Things technology on doors as a door lock. There are two ways that can be used for unlocking the lock. First is through scanning a QR Code and second is through a stick from NFC Tag in the form of a sticker that can be attached at a mobile phone. Scanning QR Code will be assisted by a camera, while the NFC Tag reader will be assisted by radio frequency waves to view the objects. Lastly, the fill in QR Code and NFC Sticker data will be assisted by an android-based application, so that the entire technology will be controller by the application. It is hoped that with the help of controlling the entire technology with this application, it will reduce and solve the existing problems regarding door locks that has been happening in our society.